Comparative Studies in Aesop’s The Lion and The Mouse and The Fox and The Cat - masofa, ima (Faculty of Letters, Dr. Soetomo University, 2019)
This article attempts to analyze Comparative Studies in Aesop’s The Lion and The Mouse and The Fox and The Cat that uses comparative studies to find differences and similarities of resolution in Aesop’s The Lion and The Mouse and The Fox and The Cat.This article uses resolution concepts that two stories have collective unconsciousness that little friends may prove great friends. This article uses comparative studies to find resolution in Aesop’s The Lion and The Mouse and The Fox and The Cat.The study aims at comparing two different literary works that describe how the two main characters from the two stories face complication and achieve resolution.The results of this article can be formulated as follows: 1) Resolution concepts can be seen in Aesop’s The Lion and The Mouse and The Fox and The Cat because they can solve their complications. The two main characters of two stories face complication when they meet a hunter, their friends come to solve complication.2) Aesop’s The Lion and The Mouse and The Fox and The Cat have similarities and differences. The similarities of the two stories are the two main characters faces complication because of hunter, themes of the two stories are friendship. Aesop’s The Lion and The Mouse and The Fox and The Cat achieve resolution by attendance of their friends. The differences of two stories are the way of the two main characters to meet a hunter. In Aesop’s The Lion and The Mouse, The lion can escape from hunter because of the mouse’s help as his friend.In Aesop’s The Fox and The Cat, a cat can escape from hunter because the cat does not follow a fox’s suggestion because his the fox has a hundred safe way from hunter but he cannot save his life from huntsmen.